The fresh groundwater lenses in the Arabian Peninsula: formative, stability and management assessments - Alrashidi, Mosaed, author; Bailey, Ryan, advisor; Grigg, Neil, committee member; Sale, Thomas, committee member; Sanford, William, committee member (Colorado State University. Libraries, 2019)
The formation of fresh groundwater lenses (FGLs) overlying denser, saline or brackish groundwater is a fascinating hydrologic phenomenon that creates groundwater supplies of great potential value for humans and ecosystems in several formation settings, such as coastal areas, atoll islands, riverine floodplains, and subterranean oases in arid regions. In particular, FGLs in subterranean oases are a critical source of freshwater supply in arid regions, due to a general lack of perennial rivers and lakes. These FGLs are in danger of salinization due to natural events and anthropogenic stresses. Although extensive research has been conducted on FGLs in general, the FGLs in subterranean oases in arid regions have received less attention. Key knowledge gaps include the quantity and frequency of natural recharge to these FGLs; reliable estimates of environmental aquifer dispersivity at the scale of subterranean FGLs; the timing of lens development; and the impact of anthropogenic activities on lens dynamics. This dissertation focuses on the FGLs of subterranean oases in the Arabian Peninsula (AP), using the Rawdatain FGL in Kuwait as a case study. Among the FGLs in the AP, the Rawdatain FGL in Kuwait is perhaps a unique candidate because of its size and the availability of extensive subsurface data for the pre-development period. The main objectives of this study are as follows: (1) estimate long-term average annual recharge for the Rawdatain FGL and investigate the timing of lens depletion due to climate change; (2) provide a realistic range of longitudinal (αL), horizontal transverse (αh), and vertical transverse (αv) dispersivity values for the aquifer; and (3) assess the impacts of historical and future anthropogenic activities and evaluate artificial recharge alternatives for lens recovery storage (LSR). In this study, a 3D density-dependent groundwater flow and solute transport model using the SEAWAT modeling code is developed using the following pre-development period calibration targets: (1) groundwater head, (2) spatially-variable total dissolved solids (TDS) groundwater concentration, (3-5) three groundwater volume targets, (6-8) three vertical thickness targets of stored groundwater of three different water quality TDS ranges (0−700, 700−1000, and 1000−2000 mg/L), and (9) geometrical shape features of the lens along cross-sections. In addition, groundwater age data of the Rawdatain FGL was used as an independent factor to constrain the dispersivity and recharge rate during the simulated period of lens development. Moreover, a sensitivity analysis was performed to explore the effects of the hydraulic conductivity, boundary conditions, and vertical transverse dispersivity on lens geometry. Based on a comparison of twelve annual recharge amount scenarios using a constant recharge mechanism (CRM) (R1 to R12: 0.2 to 5.0 million m³/year) with data targets, the R5 (0.5 million m³/year) recharge scenario is selected to represent the long-term average annual recharge. These results demonstrated that the annual natural replenishment of the Rawdatain FGL is minimal compared with its size. A macro-scale stability assessment shows that a 50% reduction in annual recharge within a 100-year time frame would reduce the lens volumes by 21%, 17% and 9% for the three water quality categories. A multi-criteria score-based method was performed to rank the best performance of 28 dispersivity sets (D1 to D28: 1 to 500 m) among all of the targets with an equal weight, on a scale of 0 to 300 x 106 m3. The results illustrated that the D16 dispersivity set (αL = 50 m: αh = 5 m: αv = 0.1 m) represents the best large-scale environmental dispersivity values for the Rawdatain FGL and can be used for analyzing the natural mixing between the ambient brackish water and fresh water. A new baseline model for the predevelopment period using a pulse recharge mechanism (PRM) was established to assess the recharge frequency along with the longitudinal dispersivity. The results revealed that the 50 m longitudinal dispersivity set and one pulse recharge every two years had the best performance, and they were selected to simulate the effects of the infrequent rainfall events and anthropogenic impacts simultaneously. During the groundwater abstraction from 1963 to 2018, the reduction in the stored volumes was 28%, 17% and 12% for the three quality categories. The future pumping scenarios (2019-2100) suggested that the 0.16×106 m3/year is a suitable alternative for long-term use, 0.5×106 m³/year)is an appropriate option for short-term use, and extraction scenarios greater than 1.0×106 m³/year will cause a remarkable degeneration of the Rawdatain FGL. Artificial recharge scenarios (2019-2028) imply that a successful LSR for the Rawdatain FGL depends on selecting appropriate well locations and amounts of injected water. For instance, the I2 alternative could achieve a 100% storage recovery within 7.5, 8 and 9 years for the three water quality categories. This study provides a first attempt to model the formation of a FGL, assess the historical anthropogenic stresses, and evaluate future management scenarios in subterranean oases in arid regions. Implementing multiple data targets and water age is a unique process of calibration that was helpful in eliminating several non-unique calibration parameters and in decreasing the uncertainty of the calibrated parameters. The methodology presented herein provides a general approach that can be extrapolated to other FGLs with similar climatic and environmental circumstances. The outputs of this dissertation enhance the understanding of the formation, stability, and management of these lenses and will be very valuable to water managers for establishing appropriate water supply plans for these valuable water reserves, leading to preferable future water security in the AP.
Keywords: calibration; freshwater lenses; management; dispersivity; arid; groundwater recharge